In this type of question, all you must do is put the values of x and y in 2x - 3y to get the answer.
2x - 3y = 2(-3) - 3(-4)
= -6 - (-12)
= 12 - 6
= 6
When x = -3 and y = -4, 2x - 3y = 6
2007-05-15 04:47:21
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
First substitute your x's and y's (-3, -4) into the equation (2x-3y). You multiply -3 * -4, and they are both negatives, the answer is +12. Next 2 * -3= -6. Add the two together [12+(-6)]= +6. Anyhow, hope you understand.
2007-05-15 11:52:28
·
answer #2
·
answered by JP 2
·
0⤊
0⤋
2(-3) - 3(-4)=6
2007-05-15 11:43:30
·
answer #3
·
answered by dwinbaycity 5
·
0⤊
0⤋
2x - 3y
2 (-3) - 3(-4)
-6 - -12
-6 + 12
6
2007-05-15 11:42:07
·
answer #4
·
answered by Anil I 4
·
0⤊
0⤋
y=6 i think
2007-05-15 11:42:32
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
THE ANSWER IS 6. IS THIS CORRECT OR WRONG? MAIUL ME SOOOOON PLZ.
2007-05-15 11:45:25
·
answer #6
·
answered by lakshmi l 1
·
0⤊
1⤋